(3JdNjU GdHjGf aj PcQ aQb Cgd GdCOjGfs - (3Ydj Hf eMeO Hf YHO Gddg GdaNQjs ((3bdYI cGT BHGO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi EUWai ef YHGOg WGFaI ef Cgd GdSfI s
(3BNQgG (B:s
(3hGYde Cf LejY GdPjf jSLOhf ddBdgI ef Ohf Gddg cGfhG jSLOhf dge SLOI hGMOI hgPG GdeNJUQ bUOfG ajg GdEjLGR s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds